Evaluasi Dampak Pelatihan 3B dalam Pemberdayaan Masyarakat Desa Bonto Mate’ne - Silvana, Silvana; Rusdi, Muhammad; Hasanuddin, Hasanuddin (Yumary: Jurnal Pengabdian kepada Masyarakat, 2025)
Purpose : This program aims to develop skills in Bonto Mate'ne Village to increase household income and community independence. Methodology: This community service activity uses a participatory approach, this study found that the community empowerment program in Bonto Mate'ne Village increased household income by 30%, with a positive impact on community social capital. Results: Partners show an increase in knowledge and skills in utilizing plastic waste into handicrafts that produce items of artistic value so that they can support local MSMEs. Conclusions: Waste recycling training increases public understanding of the urgency of sustainable waste management which is also an effort to reduce the amount of environmental pollution and reduce negative impacts on the environment. Training can also increase people's creativity in everyday life. Limitations: Lack of understanding about waste utilization and lack of attention and training in making products using waste as the main material, so that the level of environmental pollution cannot be overcome easily. Contribution: Training in making handicrafts by utilizing used goods that focuses on training and educating partners regarding the utilization of plastic waste into useful items that can open up new business opportunities for partners can also be used as supporting products for MSMEs in Bonto Mate'ne Village in realizing sustainable development programs or village SDGs in the third point, namely Healthy and Prosperous Living.